2018
DOI: 10.1016/j.vaccine.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a heat-stable rotavirus vaccine among children in Niger: Data from a phase 3, randomized, double-blind, placebo-controlled trial

Abstract: ClinicalTrials.gov: NCT02145000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(62 citation statements)
references
References 17 publications
0
62
0
Order By: Relevance
“…In both trials, children were followed for serious adverse events and episodes of acute gastroenteritis; primary analyses were conducted after a target number of cases had been reached. In Niger, the vaccine efficacy against severe rotavirus gastroenteritis was 67% [95% CI: 50–78%; per-protocol analysis at the time of primary analysis (event-driven cut-off)], and no significant differences in adverse event rates were noted in the vaccine as compared with the placebo group, though the study was not powered to evaluate differences in the risk of intussusception [28,51]. In India, the vaccine efficacy against severe rotavirus gastroenteritis in the first year of life was 33% (95% CI: 12–49%; per-protocol analysis).…”
Section: Newly Who-prequalified Rotavirus Vaccinesmentioning
confidence: 99%
“…In both trials, children were followed for serious adverse events and episodes of acute gastroenteritis; primary analyses were conducted after a target number of cases had been reached. In Niger, the vaccine efficacy against severe rotavirus gastroenteritis was 67% [95% CI: 50–78%; per-protocol analysis at the time of primary analysis (event-driven cut-off)], and no significant differences in adverse event rates were noted in the vaccine as compared with the placebo group, though the study was not powered to evaluate differences in the risk of intussusception [28,51]. In India, the vaccine efficacy against severe rotavirus gastroenteritis in the first year of life was 33% (95% CI: 12–49%; per-protocol analysis).…”
Section: Newly Who-prequalified Rotavirus Vaccinesmentioning
confidence: 99%
“…73 Only one case of intussusception was reported, 542 d after receipt of the third dose. 74 The vaccine group experienced 395 serious adverse events, compared to 419 serious adverse events in the placebo group; this difference was not significant. 74 Adverse events between the two groups were comparable, with 1474 (72.1%) participants receiving ROTASIIL and 1456 (71.1%) participants receiving placebo experiencing at least one adverse event (p = .49) in the follow-up period; ROTASIIL was found to be safe.…”
Section: Phase IIImentioning
confidence: 91%
“…72 Secondary outcome measures were rotavirus gastroenteritis, hospitalization due to rotavirus gastroenteritis, hospitalization of any cause (adverse effects or rotavirus gastroenteritis), serious adverse events, and anti-rotavirus IgA sero-response rates and geometric mean titers. [72][73][74] The study found an efficacy of 66.7% (95% CI: 49.9, 77.9) against severe rotavirus gastroenteritis. 73 Only one case of intussusception was reported, 542 d after receipt of the third dose.…”
Section: Phase IIImentioning
confidence: 99%
“…We conducted a double-blind, placebo-controlled randomized phase III event-driven trial in Madarounfa, Niger, to assess the efficacy and safety of Rotasiil (Serum Institute of India, Pune, India) against SRVGE in healthy infants (ClinicalTrials.gov identifier: NCT02145000). Primary efficacy and safety results were previously reported after accumulation of the target number of primary endpoint cases [ 11 , 12 ]. In brief, among the 3,508 infants included in the per-protocol efficacy analysis, there were 31 and 88 cases of SRVGE in the vaccine and placebo group, respectively (2.14 and 6.44 cases per 100 person-years; vaccine efficacy 66.7%, 95% CI 49.9% to 77.9%).…”
Section: Methodsmentioning
confidence: 99%